Software-Defined Networking and Security : From Theory to Practice - Huang, Dijiang (CRC Press)
Contiene: 1) Introduction of Computer Networks; 2) Virtual Networking; 3) Redes Definidas por Software (Software Defined Networks, SDN) y Virtualización de Funciones de Red (Network Functions Virtualization, NFV); 4) Network Security Preliminaries; 5) SDN and NFV Security; 6) Microsegmentation; 7) Moving Target Defense (MTD); 8) Attack Representation; 9) Service Function Chaining; 10) Security Policy Management in Distributed SDN Environments; 11) Intelligent Software-Defined Security.